The Level of Saliva Glutathione in Moderate Gingivitis Patients Increases After Gargling with 5% Cosmos (Cosmos caudatus) Extract - Malreen Kaur Harban Singh; Regina Titi Christinawati Tandelilin; Juni Handajani (Indonesian Dental Association, 2021)
Introduction: Gingivitis is an inflammation of the gums caused by bacterial plaque accumulation producing reactive oxygen species (ROS). Reactive oxygen species is a harmful by-products from aerobic metabolisms of mitochondria, that when accumulated can cause large variety of diseases. Antioxidants can counter ROS activities. Oxidative stress may occur due to an imbalance between ROS and antioxidants. Glutathione (GSH) is an antioxidant that protects cells against oxidative damage. Cosmos caudatus is rich in antioxidants due to its flavonoid and phenolic contents. Objective: The aim of this study was to detect the concentration of saliva GSH in moderate gingivitis patients after gargling with a solution containing 5% Cosmos (Cosmos caudatus) extract. Methods: Twenty subjects with moderate gingivitis were divided into two groups—the treatment and control group—by drawing lots in a randomized controlled trial. The treatment group gargled with 5% Cosmos extract whereas the control group gargled with Chlorhexidine 0.1%. Each subject was required to gargle for 60 seconds every morning and night, for five days consecutively. The GSH level was measured before and after gargling on the sixth day after treatment using a spectrophotometer with wavelength of 412 nm. Data was analyzed using an independent T-Test (p <0.05). Results: The study showed there was significant difference between the saliva GSH level of each group before and after gargling; moreover, after gargling with the solutions, no significant difference of saliva GSH was found when compared between the treatment group and the control group. Conclusion: The level of saliva GSH increases after gargling using 5% Cosmos extract and has the same effect with Chlorhexidine 0.1%.